PENGEMBANGAN PARIWISATA PULAU LEMBEH DI KOTA BITUNG - KOKODJU, HAPSA MUTIAH; RARES, JOYCE JACINTA; KIYAI, BURHANUDDIN (Sam Ratulangi University, 2019)
The development of the world of tourism has undergone various changes, both changes in thepattern, shape and nature of activities, as well as the encouragement of people to travel, ways of thinkingthat can provide rapid economic growth. Tourism development is not only directed at attracting foreigntourists but also domestic tourists. In line with the development of the world of tourism which appears to beincreasing, as well as the existence of areas that have the potential to become tourism objects, therefore theselection of activities or development of facilities must be measured in a way that does not conflict withsocial and ecological values. The purpose of this study was to find out the development of Lembeh Islandtourism in Bitung City. The theory used is development and tourism. The research method used is aqualitative method that is trying to find answers to questions related to tourism development. These questionsrequire descriptive answers that describe the facts about the problems being investigated as well as therational interpretation of various findings in the field while analyzing all the conditions at the research site.Based on the results of the research namely the development of Lembeh Island tourism in Bitung City, sometourist sites have not developed and due to lack of government attention, one of them is the limited facilitiesavailable at Lembeh Island tourist attractions in Bitung City.Keywords: Development, Tourism, Island